LITERATURE REVIEW ON THE DEVELOPMENT OF STUDENT WORKSHEET BASED ON MIKIR STRATEGIES TO IMPROVE NUMERACY ABILITIES - Krisni Suhardiyani; Sri Subanti; Budi Usodo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Mathematical numeracy skills are essential competencies needed by students to understand and solve contextual problems in everyday life. However, various assessment results indicate that the numeracy skills of junior high school students in Indonesia are still relatively low, necessitating innovation in mathematics learning. One effort that can be done is through the development of Student Worksheets (SW) that are systematically designed and oriented towards students' thinking processes. This article aims to systematically review the research literature related to SW development, mathematical numeracy skills, and the potential integration of the MIKiR (Experience, Interaction, Communication, and Reflection) strategy in junior high school mathematics learning. The research method used is a systematic literature review of journal articles. The results of the study indicate that contextual SW can improve students' numeracy skills, but most studies have not integrated learning strategies explicitly into the SW design. This study confirms a research gap related to the development of SW based on the MIKiR strategy to improve junior high school students' mathematical numeracy skills